Dimensions of aberrant driving behaviour and their relation to crash involvement for drivers in New Zealand. (October 2019) - Sullman, Mark J.M.; Stephens, Amanda N.; Taylor, Joanne E.
Highlights: The Driver Behaviour Questionnaire was administered in two independent samples. The four factor solution was confirmed using exploratory factor analysis in the first sample. Confirmatory factor analysis confirmed the four factors in the second independent sample. All four DBQ factors were significantly related to crashes in the first sample. In the second sample the number of crashes reported was very low. Abstract: The Driver Behaviour Questionnaire (DBQ) is the most commonly used framework for investigating the relationship between self-reported driving behaviour and crash involvement. However, in spite of the fact that the scale is almost 30 years old, the factor structure of the scale and relationship to crashes in New Zealand remains under-researched. The present study set out to establish the factor structure of the DBQ in a sample of New Zealand private vehicle drivers and to examine the adequacy of this factor structure in an independent second sample of New Zealand drivers. Using exploratory factor analysis, the first sample ( n = 860, M age = 39.3, 44% females) produced a factor structure that broadly supported the four hypothetical factors of errors, violations, aggressive violations and lapses. This factor structure was supported in a second sample from the New Zealand electoral roll ( n = 441, M age = 53.4, 55% females), using confirmatory factor analysis. There were a number of differences in the relationships that the DBQ factors had with the demographic and descriptive variables. In the first sample, all four of the DBQ factors were significantly related to crash involvement. In contrast, none of the DBQ factors were related to crash involvement in the second sample, possibly due to the very small number of crashes reported. However, these differences are likely due to differences in the demographic composition of the two samples. The present study suggests that the DBQ is a valid measure of aberrant driving behaviour in New Zealand and this consists of errors, violations, aggressive violations and lapses.